Indigenous Australian Youth Futures Living the Social Determinants of Health - Burbank, Victoria; Chenhall, Richard; Senior, Kate (ANU Press, 2021)
Adolescents are at a critical life stage where they will soon be able to contribute to the wellbeing of humankind, or do it great harm. Consequently, it is vital that the challenges and possibilities of adolescence be well understood and addressed. In Australia, such understanding is urgently needed with respect to Aboriginal adolescents. Not only must they adjust to their changing bodies and minds, but they must negotiate these changes within a context usually characterised by racism and poverty. They must also do this within intercultural environments that include the disparate and sometimes incompatible beliefs and practices of their multicultural populations. The chapters in this collection address these challenges to Aboriginal adolescents in the Northern Territory and the intercultural contexts in which they take place. Their discussions include the adolescents' experiences with health and health care, education, and the criminal justice system. They also address their hopes, dreams, plans and politics, engagement with social media, food preferences and nutrition, engagement with language, family, and changing mores affecting sexual behaviour and marriage. The book aims to provide readers with a greater understanding of the day-to-day lives of Aboriginal adolescents, and some of the adults who care for or neglect them. It seeks to provide readers with a better understanding of the circumstances, processes and factors that affect adolescent health, wellbeing and future prospects in their intercultural environments, and glimpse the multiplicity of these circumstances, processes and factors and the complexity of their interaction.